Rapid health technology assessment of six non-ergot dopamine-receptor agonists for the treatment of early Parkinson’s disease - Lv, Jieqiong; Fu, Hongbo; Zhou, Yanqiong; Li, Wenwei; Zhang, Jiaxin; Zhou, Zhihua; Lai, Sha (Frontiers in Pharmacology, 2025)
PurposeSix non-ergot dopamine -receptor agonists (NEDAs), including pramipexole extended-release (ER), pramipexole immediate-release (IR), rotigotine patch, piribedil, ropinirole prolonged-release (PR), and ropinirole IR, are frequently used to treat early Parkinson’s disease (PD). However, there is a paucity of comparative information about them. For making rational drug selections, six NEDAs were evaluated using a rapid health technology assessment method.MethodsAccording to the rapid guidelines for drug evaluation and selection in Chinese medical institutions (the Second Edition), the pharmacological properties, efficacy, safety, economy, and other attributes of six NEDAs were scored on a percentage system.ResultsThe composite scores of the six NEDAs are presented as follows: 74.99 points for pramipexole ER, 74.90 points for piribedil, 72.40 points for pramipexole IR, 70.78 points for rotigotine patch, 69.06 points for ropinirole PR and 68.41 points for ropinirole IR.ConclusionBased on our comprehensive multi-criteria assessment, pramipexole ER, pramipexole IR, rotigotine patch, and piribedil are strongly recommended for inclusion in the formularies of medical institutions as therapeutic options for patients with early PD.